Comunicação e ativismo transnacional de bolivianos no Brasil: mobilizações políticas e narrativas contra-hegemônicas no marco do golpe de Estado na Bolívia em 2019 - Almeida, Gabriel Soares de (2021)
This research’s goal is to analyze the communication and transnational activism forms of organization through networks of Bolivian immigrants in Brazil and their practices of political mobilization through counter-hegemonic narratives in the context of the coup d’État against Evo Morales in 2019. We seek to comprehend the role of social communication, technologic and migration networks in such processes, and how they intertwine in those individuals’ communicational and political actions that articulate both their countries of origin and destination, as well as how they use the Information and Communication Technologies (ICTs). Our research methodology covers the collection and analysis of communication materials from transnational activists’ networks against the Bolivian coup d’État, semistructured interviews with two activists, and participation in one of the Bolivians’ demonstrations in Brazil in November of 2019 against the coup. Among this research’s results, we highlight that the transnational activists against Áñez’s government produce spaces for mobilization and political action through networks, whose communication dimensions establish disputes for hegemony in three axes: 1. through denunciations to the hegemonic coup-supporting narratives; 2. through the production of counter-hegemonic narratives by said activists; 3. through calls to action. These forms of communicational action support dynamics of articulation between actors that establish forms of political participation and of taking part in the sensible. Therefore we comprehend the forms through which transnational activism constitutes spaces for political participation and struggles for hegemony, by the articulation of narratives and uses of the digital platforms for communication.